2019
DOI: 10.1021/acsomega.9b00278
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Thermal Oxidative Stabilization on the Performance of Lignin-Based Carbon Nanofiber Mats

Abstract: Lignin is a renewable biopolymer considered as a potential precursor for low-cost carbon materials. Thermal oxidative stabilization (TOS) is an important processing step to maintain fiber geometry during carbonization, yet the impact of  TOS on the properties of lignin-based carbon materials has not been clearly identified in the literature. Yield, change in fiber diameter/distribution, elemental composition, and mechanical properties were explored for both stabilized and carbonized lignin fibers. Vibrational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…As seen in Table 2, the electrical conductivity of the lignin bres increased with carbonisation temperature from 1000°C to 1200°C and 1500°C. The lignin bres that were carbonised at 1500°C show electrical conductivity comparable to those reported in literature for softwood Kraft lignin (230 S m − 1 ) 2,52 .…”
Section: Electrical Conductivity Of Electro-spun Asl-esl Carbonised Lsupporting
confidence: 83%
See 1 more Smart Citation
“…As seen in Table 2, the electrical conductivity of the lignin bres increased with carbonisation temperature from 1000°C to 1200°C and 1500°C. The lignin bres that were carbonised at 1500°C show electrical conductivity comparable to those reported in literature for softwood Kraft lignin (230 S m − 1 ) 2,52 .…”
Section: Electrical Conductivity Of Electro-spun Asl-esl Carbonised Lsupporting
confidence: 83%
“…The ratio of intensities of D to G are represented by I D /I G whilst A D /A G shows the ratio of areas. 51,52 Results…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…However, when the content of the thermal conductive filler is too high, the granular material is prone to agglomeration, which makes the composite have certain defects and destroys the mechanical property. As a one-dimensional (1D) material, CF has high thermal conductivity in the axial direction of the fiber [ 36 , 37 ]. The CF filaments easily overlap each other inside the matrix to form a denser heat-conducting network [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…13,24 Recently, Cho et al showed that the stabilization temperature and heating rate have only a minor effect on the structure of carbonized electrospun nanober mats from sowood lignin. 25 These differences did not correlate with changes in mechanical performance. 25 Various sowood and hardwood lignin-derived carbon nanobers (LCNFs) were tested in supercapacitors operating in different electrolytes and cell congurations.…”
Section: Introductionmentioning
confidence: 95%
“…25 These differences did not correlate with changes in mechanical performance. 25 Various sowood and hardwood lignin-derived carbon nanobers (LCNFs) were tested in supercapacitors operating in different electrolytes and cell congurations. [26][27][28][29][30] To date, a clear inference concerning the reasons for superior performance of one lignin compared with another is out of reach.…”
Section: Introductionmentioning
confidence: 95%